TCR mimic compounds for pHLA targeting with high potency modalities in oncology - Gerber, Hans-Peter; Presta, Leonard G. (Frontiers in Oncology, 2022)
pHLA complexes represent the largest class of cell surface markers on cancer cells, making them attractive for targeted cancer therapies. Adoptive cell therapies expressing TCRs that recognize tumor specific pHLAs take advantage of the unique selectivity and avidity of TCR : pHLA interactions. More recently, additional protein binding domains binding to pHLAs, known as TCR mimics (TCRm), were developed for tumor targeting of high potency therapeutic modalities, including bispecifics, ADCs, CAR-T and -NK cells. TCRm compounds take advantage of the exquisite tumor specificity of certain pHLA targets, including cell lineage commitment markers and cancer testis antigens (CTAs). To achieve meaningful anti-tumor responses, it is critical that TCRm compounds integrate both, high target binding affinities and a high degree of target specificity. In this review, we describe the most advanced approaches to achieve both criteria, including affinity- and specificity engineering of TCRs, antibodies and alternative protein scaffolds. We also discuss the status of current TCRm based therapeutics developed in the clinic, key challenges, and emerging trends to improve treatment options for cancer patients treated with TCRm based therapeutics in Oncology.